Thigh positioned wearable resistance improves 40m sprint performance: A longitudinal single case design study - Macadam, P.; Nuell, S.; Cronin, J. B.; Diewald, S.; Neville, J. (Journal of Australian Strength and Conditioning, 2019)
A five-week sprint training program with wearable resistance attached to the thighs provides a sprint specific training means for rotational overload and subsequent speed adaption with increased horizontal force production (7.1%) resulting in faster times (2.4-3.4%) over all distance markers during 40 m sprint-running.